Cash Waqf Optimization and the Improvement of Higher Education Quality: A Comparative Study between the Islamic University of Indonesia and IPB University - Fikri Hilmansyah; Yuli Yasin; Mualimin Mochammad Sahid (Mauriduna : Journal of Islamic Studies, 2026)
This study analyzed  the optimization of cash waqf in improving the quality of higher education, using Universitas Islam Indonesia (UII) as a case study from the perspective of Islamic Economic Law. This study employed a qualitative normative-empirical approach with analysis of the 2024 Financial Report of the UII Waqf Board Foundation and a comparative study with Bogor Agricultural Institute (IPB), this research identified cash waqf management strategies and their implications for social goals. The reserach findings indicated that cash waqf management at UII reflected a structured management system oriented toward the sustainability of funds. These practices have successfully maintained the sustainability of the principal funds (hifz al-mal), yet have resulted in a limited proportion of benefit distribution. A comparison with IPB revealed a strategic difference in balancing the goals of sustainability and social impact, with IPB demonstrating more diverse program innovation and impact-oriented reporting. This study contributed by presenting a comparative analysis model for the implementation of cash waqf, providing insights into the strategic balance between investment and distribution to optimize the achievement of maqāṣid al-sharī‘ah and SDG-4. The application of these findings can serve as a reference for higher education waqf institutions in formulating more innovative and impact-oriented management strategies.